The Development of Nursing System for Critical ill patients with covid-19 at Sakon Nakhon Hospital - Chaiyara, Saithip; Nadsantia, Pailin; Srithong, Isara; Sirimontri, Jeerawan (Journal of The Royal Thai Army Nurses, 2023)
The objectives of this research were to develop and to evaluate a nursing system for critically ill patients with COVID-19 at Sakon Nakhon hospital by carrying out six stages. The sample were a head of nurse, heads of nursing department, heads of nursing ward and registered nurses, totally 52 nurses and 152 of critically ill patients with COVID-19. The research instruments were the nursing practice guideline, the nursing competency assessment form, the nursing demonstration, the group discussion guideline, the critically ill patient data collection from and the satisfaction assessment formม The data were analyzed using descriptive statistics with Wilcoxon Signs Ranks test and Chi square test. The results found that 1) The nursing system consisted of 3 components: 2 phases of nursing practice guideline, 9 aspects of nursing competency and 4 aspects of nursing demonstration. 2) The post-development results showed that the adverse incidence rates such as death, cardiac arrest, shock, acute respiratory failure and acute kidney injury were statistically significant differences (P<.05). The nursing competency was statistically significant difference (P<.05), also the nursing demonstration found that nurses follow the nursing system as 88.24% and the overall satisfaction towards the nursing system was at highest level (mean = 4.53, SD = 0.51).